Metal forming ensures innovation and future in Europe - Geiger, Manfred; Merklein, Marion; Tolazzi, Massimo (Proceedings of the 8th International Conference on TEchnology of Plasticity (ICTP), 2005)
The role of the European Union in the field of research funding is becoming more and more important for the strategic choices of the single countries of the Old Continent. The new framework programs receive increased investments and at the same time give precise the-matic areas for the possible application of research proposal. However it can be surprisingly observed that topics concerning metal forming technology have strongly lost consideration in the 6th Framework Program. Metal forming remains in fact a key technology, being es-sential for almost all the manufacturing processes and fundament of the most important aspects of our society: mobility, health, communication. The extraordinary developments of the Industrial Society in the 20th Century showed the importance and potential of a scien-tifically driven technology development, in which an idea can become an invention, be ap-plied and completely change the world in few decades. If we want to ensure our future we cannot give up innovation and research, especially in metal forming; on the contrary we should properly fund them at a public level. There are in fact many promising innovations in metal forming, which are emerging in these years and will be presented in this paper, which may become key technologies for the manufacturing of tomorrow.
LFT Import::2019-08-05 (1219)
Keywords: Funding; Innovation; Metal forming; Research